Toscana virus isolated from sandflies, Morocco - Es-sette, Nargys (Parasit Vectors, 2015)
To investigate the transmission of phleboviruses, a total of 7,057 sandflies were collected in well-known foci of cutaneous leishmaniasis and were identified to species level according to morphological characters. Collected sandflies were tested by Nested PCR for the presence of Phleboviruses and subsequently by viral isolation on Vero cells. The corresponding products were sequenced. Toscana virus was isolated, for the first time, from 5 pools of sandflies. Hence, Toscana virus should be considered a potential risk that threatens public health and clinicians should be aware of the role of Toscana virus in cases of meningitis and encephalitis in Morocco.